(untitled) (Journal of the College of Basic Education, 2022)
The Qur’anic text is miraculous in every aspect and magnetically attracts the researcher towards it in order to It touches the citizens of radiance in its expressive and creative levels, especially the aspects that give the researcher wide and deep fields in order to draw whatever he wants from the sciences of the Holy Qur’an, and through my follow-up to the subject Studying the verbal, intangible, present, and other conjunctures in the Arabic sentence. in effect and function, which is known as the contextual presumption, and it is also called the major contextual presumption.